36. Sensitivity of single fibre electromyography in ocular myasthenia. Issue 4 (April 2016) - Donadio, V.; Giannoccaro, M.P.; Di Stasi, V.; Avoni, P.; Liguori, R.
Abstract : The diagnosis of ocular myasthenia (OM) can be challenging due to the mildness of symptoms and to the absence of a gold diagnostic standard test. In several studies single fibre electromyography (SFEMG) showed a sensitivity of 0.86–0.99 for the diagnosis of OM. However these studies presented some methodological limitations. Our aim is to determine the diagnostic sensitivity of SFEMG in OM. We studied 157 consecutive patients diagnosed with OM on the basis of the presence of at least one of the following criteria: (1) positive edrophonium test; (2) abnormal repetitive nerve stimulation; (3) positive antiacetylcholine receptor antibodies; (4) improvement with corticosteroid therapy. Other diseases presenting with ptosis/diplopia were excluded. Stimulation SFEMG was performed on orbicularis oculi (S-SFEMG) in all cases and on the frontalis during voluntary activation (V-SFEMG) in 120 patients. In the whole population S-SFEMG was positive in 71% of cases whereas V-SFEMG was positive in 62% of cases. In patients with isolated ptosis (45%) S-SFEMG and V-SFEMG were positive in 87% and 85% of cases, respectively. In patients with isolated diplopia (31%) S-SFEMG and V-SFEMG resulted abnormal in 27% and 3% of patients, respectively. In patients with ptosis and diplopia (24%) both S-SFEMG and V-SFEMG were positive in 100% of cases. SFEMG showed a lower sensitivity than previously reported. However, sensitivity appears to be highly variable in relation with the clinical phenotype, being particularly low in patients presenting with isolated diplopia. S-SFEMG on orbicularis oculi is more sensitive than V-SFEMG on frontalis.